Latent profiles and determinants of postoperative sleep quality in elective surgery patients - Binxu Yang; Jingjing Li; Dan Feng; Jing Gong; Yifei Yang; Xusihong Cai; Shuwen Huang; Lorna Kwai Ping Suen; Puzhong Gao; Qingde Wa; Jing Zhou (Scientific Reports)
Abstract It is crucial to determine the potential subgroups of sleep disturbances in patients undergoing elective surgery based on the importance of symptom clusters and individual characteristics in order to develop targeted symptom management plans. This study explored the potential categories of postoperative sleep disturbances in patients undergoing elective surgery through latent profile analysis, and explored the influencing factors of each category. A total of 400 eligible elective surgery patients were included in the analysis, and three potential subgroups were identified: mild sleep disturbance group (c1 = 140,35.0%), moderate sleep sleep disturbance group (c2 = 177,44.2%), and severe sleep disturbance group (c3 = 83,20.8%). It was found that the higher the BMI, the greater the probability of patients belonging to the moderate sleep disturbance group (OR = 1.114, P = 0.002) and the severe sleep disturbance group (OR = 1.258, P < 0.001),the longer the duration of anesthesia the greater the likelihood of patients belonging to the severe sleep disturbance group (OR = 1.004,P = 0.011), the greater the pain the greater the probability of patients belonging to the moderate sleep disturbance group (OR = 1.590,P < 0.001) and severe sleep disturbance group (OR = 1.785,P < 0.001), and the higher the anxiety level the greater the probability that patients were in the moderate sleep disturbance group (OR = 1.135,P = 0.007) and severe sleep disturbance group (OR = 1.261,P < 0.001).